The American jail: cornerstone of modern corrections - Cornelius, Gary F. (Pearson/Prentice Hall, 2008)
The history and development of today's jail -- Jail security -- Jail climate -- Booking and initial intake -- Classification and inmate housing -- Jail programs and services -- The jail population : profile and special categories -- Jail staff -- Jails and the courts -- Jail standards -- Jails and community corrections -- The future of the American jail